Influences on indoor environmental trigger remediation uptake for children and young people with asthma: A scoping review. (7th December 2022) - Lewis, Grace; Milnes, Linda; Adams, Alexandra; Schwarze, Jürgen; Duff, Alistair
Abstract: Introduction: Children and young people (CYP) with asthma can benefit from reduced exposure to indoor environmental allergens and triggers but may not consistently have avoidance strategies implemented. To inform future interventions to increase trigger and allergen avoidance and enhance asthma control, a greater understanding of the influences on avoidance behaviours is necessary. Methods: A systematic scoping review was selected to summarize evidence on what influences family uptake of indoor environmental asthma trigger avoidance strategies for CYP with asthma and identify research gaps. Primary studies of any design, including CYP (≤18 years) with asthma, and/or parent‐carers, available in English and conducted since 1993, were eligible. Searches included nine databases, hand‐searching reference lists and citation searching. Findings: Thirty‐three articles were included and are summarized narratively due to heterogeneity. Influences appear complex and multifactorial and include barriers to strategy uptake, health beliefs and personal motivation. Research specifically related to family understanding of allergic sensitisation status and exposure risks, and how these may inform avoidance implementation is required. Patient and public involvement (PPI) was not reported in included articles, although two studies used participatory methods. Conclusion: There is limited research on family asthma trigger management, particularly what influences current management behaviours. Variation in families' ability to identify important triggers, understand exposure risk and consistently reduce exposures warrants further exploratory research to explain how families reach avoidance decisions, and what future interventions should aim to address. Further PPI‐informed research to address such gaps, could enable theory‐based, person‐centred interventions to improve the uptake of asthma trigger remediation. Patient or Public Contribution: An asthma‐specific PPI group contributed to the decision‐making for the funding for the wider project this review sits within. The findings of this scoping review have informed the subsequent phases of the project, and this was discussed with PPI groups (both adult and CYP groups) when proposing the next phases of the project.